1983
DOI: 10.1021/bi00289a022
|View full text |Cite
|
Sign up to set email alerts
|

Specific receptor sites for 1-0-alkyl-2-0-acetyl-sn-glycero-3-phosphocholine (platelet activating factor) on rabbit platelet and guinea pig smooth muscle membranes

Abstract: By using tritiated 1-O-alkyl-2-O-acetyl-sn-glycero-3-phosphocholine (3H-PAF), we have directly identified its specific binding sites on rabbit platelet plasma membranes. The equilibrium dissociation constant for 3H-PAF is 1.36 (+/- 0.05) X 10(-9) M at 0 degrees C. The number of binding sites is 1.61 (+/- 0.34) X 10(12)/mg of membrane, which corresponds to approximately 150-300 receptors/platelet (depending on membrane vesicle orientation). Binding of 3H-PAF to rabbit platelet plasma membrane is rapid (t1/2 les… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
51
1
13

Year Published

1986
1986
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 230 publications
(69 citation statements)
references
References 38 publications
4
51
1
13
Order By: Relevance
“…1984;Piper & Stewart, 1986;Fiedler et al, 1987). However, not affect the the vasodilator effect, when observed, was not altered by FPL-)Opmol LTC4 55712 (Feuerstein et al, 1984;Fiedler et al, 1987 (Piper & Stewart, 1986; us to examine Man et al, 1990) ts, Specific binding of radiolabelled PAF was first demonn the coronary strated in platelets (Valone et al, 1982;Hwang et al, 1983) and subsequently demonstrated in a number of tissues (see review of Braquet et al, 1987). The binding of PAF showed the presence of high affinity sites, stereospecificity and saturation kinetics.…”
Section: Discussionmentioning
confidence: 99%
“…1984;Piper & Stewart, 1986;Fiedler et al, 1987). However, not affect the the vasodilator effect, when observed, was not altered by FPL-)Opmol LTC4 55712 (Feuerstein et al, 1984;Fiedler et al, 1987 (Piper & Stewart, 1986; us to examine Man et al, 1990) ts, Specific binding of radiolabelled PAF was first demonn the coronary strated in platelets (Valone et al, 1982;Hwang et al, 1983) and subsequently demonstrated in a number of tissues (see review of Braquet et al, 1987). The binding of PAF showed the presence of high affinity sites, stereospecificity and saturation kinetics.…”
Section: Discussionmentioning
confidence: 99%
“…42 In the present study, stellate cells from cirrhotic liver had a 2.6-fold increase in PAF receptor density and a 1.6-fold increase in PAF induced PGE 2 synthesis relative to control cells, matching the augmented sensitivity to PAF of the intact organ. The smooth muscle component of the hepatic vasculature may also contribute [51][52][53] to PAF induced increases in portal pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Binding sites for PAF have been shown to be present on a number of cell types including platelets [12-141, neutrophils [15,16], guinea pig smooth muscle membranes [12] and lung tissue [ 171, suggesting that PAF exerts its effects via a specific extracellular receptor. Investigation of the postreceptor events intrinsic to PAF action has been carried out mainly in platelets where PAF can elevate the intracellular calcium level, [Ca'+]i, although it stimulates shape change even when [Ca*+]i is suppressed [18].…”
Section: Discussionmentioning
confidence: 99%
“…Hwang et al [12] have shown specific binding sites for PAF on several tissues, including rabbit ileal smooth muscle membranes, with a dissocation constant in the nanomolar range. Our findings support the view that these sites are functional receptors, the stimulation of which results in phospholipase C-mediated degradation of PtdInsPz and the subsequent production of InsPJ and 1,Zdiacylglycerol.…”
Section: Discussionmentioning
confidence: 99%